Systematic Review of Food Addiction as Measured with the Yale Food Addiction Scale: Implications for the Food Addiction Construct - Penzenstadler, Louise; Soares, Carina; Karila, Laurent; Khazaal, Yasser (Current Neuropharmacology, 2019)
Background: The concept of food addiction attracts much interest in the scientific community. Research is mainly based on the Yale Food Addiction Scale (YFAS), a tool developed to assess food addiction. Substance use disorder criteria have been used to develop this scale. Objective: The aim of this paper was to review the clinical significance of food addiction diagnoses made with the YFAS and to discuss the results in light of the current debate on behavioral addictions. Methods: We performed a systematic review of the studies that assessed food addiction with the YFAS published between January 2014 and July 2017 by searching the electronic databases PsycINFO, MEDLINE, and PsycARTICLES. Results: Sixty publications were included in the analysis. Thirty-three studies examined nonclinical samples and 27 examined clinical samples. All studies used YFAS scoring results to define food addiction. The prevalence of food addiction according to the YFAS varied largely by the studied samples. In general, a higher body mass index and the presence of eating disorders (EDs), especially binge eating disorder (BED), were associated with higher YFAS scores. Conclusion: The concept of food addiction has not been established to this day although it can be grouped with other EDs such as BED. More research is needed to understand this behavior and the differences between food addiction and other EDs. The criteria for food addiction should be revisited in light of the concepts currently used to examine behavioral addictions.
Keywords: obesity